REFLECȚII ETICE ASUPRA CONCEPTULUI DE „DIZABILITATE” (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Ethical Reflections upon the Concept of “Disability”The concept of “disability” has met a profound revision over the years, both from a scientific and judicial point of view, and from a cultural and social one. The actual change of the concept of “disability” took place along with the adoption in 2006, of The Convention on the Rights of the Persons with Disabilities, according to which disability is not a negative feature of the human being, but a problem of the entire society, which cannot adapt to the individual necessities of the person. The present paper aims to present some reflections on the evolution, from a legislative and a scientific point of view, of the concepts of “infirmity” and “disability”, emphasizing the ethical implications that the adoption of some perspectives about disabilities could have.